Causal Effects of Career-Technical Education on Postsecondary Work Outcomes of Individuals with High-Incidence Disabilities. Issue 2 (2nd April 2016) - Lee, Heok; Rojewski, Jay W.; Gregg, Noel
ABSTRACT: Using data from the National Longitudinal Transition Study-2, a propensity score analysis revealed significant causal effects for a secondary career and technical education (CTE) concentration on the postsecondary work outcomes of adolescents with high-incidence disabilities. High school students identified as CTE concentrators (three or more high school credits in a single career pathway) were more likely to be employed full-time after high school completion than non-CTE concentrators earning fewer CTE credits. Results support and extend past descriptive and correlational studies by detecting a direct causal link between CTE and postsecondary work outcomes.